Molecular Structure and Electronic Properties of Porphyrin-Thiophene-Perylene Using Quantum Chemical Calculation - Tatiya Chokbunpiam; Patchanita Thamyongkit; Oraphan Saengsawang; Supot Hannongbua (International Journal of Photoenergy)
This study aimed to design a new series of compounds consisting of a porphyrin macrocycle linked to a perylene unit via a thiophenic bridge. The structural and electronic properties of the molecules, and the effects of mono- and di-substituents R on C3 and R′ on C4 of the thiophene ring were investigated using a quantum calculation approach. The results from the method validation revealed that using the density functional theory approach at B3LYP/6–31G(d) data set was the optimal one, considering the accuracy attained and maintaining the computer time required within tractable limits. The results from the B3LYP/6–31G(d) approach indicated that significant changes of the torsion angle between the molecular planes of the porphyrin and perylene rings, compared to that of the unsubstituted derivatives, were found in the di-substituted systems bearing R = R′ = −OCH3 and −NH2, and in a mono-substituted system having R = −H and R′=−NH2. The symmetric di-substitution does not provide a significantly lower HOMO-LUMO energy gap (ΔEg). Noticeable decreases in ΔEg were found only with the substitution patterns of: R, R′ = −OCH3, −H; −OH, −H; −N(CH3)2, −H; −H, −NH2. UV-visible spectra of all derivatives exhibited characteristic absorption maxima of the free bases of porphyrin and perylene.